The impact of economic transformation and the credibility of planning control on agricultural land values - Khalid, Haniza; Lloyd, Timothy Adrian; Morgan, Christopher Wyn (Deutscher Fachverlag GmbH, 2013)
This paper develops a hedonic model of agricultural land prices to investigate the efficacy of planning controls, whose raison d’être is to regulate the conversion of farmland. While development (commercial, industrial and residential) potential of farmland affects agricultural land values in all countries, its impact is potentially more acute in Newly Industrialised Countries where development pressure is strong and planning law is often weakly enforced. In the Malaysian land market, which epitomises this situation, State Authorities have approved a large number of applications to convert land from agriculture to development, such that the market is inclined to behave as if planning control lacks credibility. To investigate the influence of 'development potential' on land legally designated as agricultural in Malaysia, an extensive dataset of over 2,000 land sales has been assembled. Using this database we attempt to estimate the effect – the development rent – on land price, which turns out to be high, exceeding 400% of agricultural value in some cases. From there, we draw some conclusions regarding the efficacy of existing planning controls and the implications of such a high premium.